2018
DOI: 10.5539/jel.v7n4p225
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Primary School Teachers’ Attitudes Towards Teaching Mathematics

Abstract: The aim of the study is to determine prospective primary school teachers' attitudes towards teaching mathematics. The study is designed according to model of survey in the descriptive type. A total of 236 prospective primary school teachers were examined in order to investigate the effect of gender and program differences on their attitudes towards teaching mathematics. In the study, the questionnaire "Teaching Mathematics" was used to collect the data from prospective teachers. The results revealed that the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 5 publications
(3 reference statements)
0
4
0
4
Order By: Relevance
“…This result can be taken to mean that junior high school teachers have better attitudes toward using technology in mathematics teaching because junior high school mathematics teachers were exposed quite a longer time than the primary mathematics teachers. However, this is denied by Tabuk (2018) in her study on teachers' attitudes, which revealed that grade level is not a significant factor in attitude scores.…”
Section: Resultsmentioning
confidence: 92%
“…This result can be taken to mean that junior high school teachers have better attitudes toward using technology in mathematics teaching because junior high school mathematics teachers were exposed quite a longer time than the primary mathematics teachers. However, this is denied by Tabuk (2018) in her study on teachers' attitudes, which revealed that grade level is not a significant factor in attitude scores.…”
Section: Resultsmentioning
confidence: 92%
“…Buna göre cinsiyetin sınıf eğitimi lisans öğrencilerinin tutumlarında önemli bir etkiye sahip olmadığı; kadın ve erkek öğrencilerin matematik öğretimine ilişkin benzer tutumlara sahip oldukları söylenebilir. Bu kapsamda, ilgili literatür incelendiğinde bu araştırma sonucu ile benzerlik gösteren araştırmalar olduğu gibi (Bulut Üner, 2018;Göloğlu Demir, 2011;Tabuk, 2018); araştırma sonucu ile çelişen araştırma bulguları da (Fennema & Sherman, 1977;Nisbet, 1991;Reyes, 1984;Tabuk & Tabuk, 2018b) göze çarpmaktadır. Bu bağlamda örneğin Tabuk ve Tabuk, (2018b) sınıf ve okul öncesi bölümlerinde öğrenim gören lisans öğrencilerinin matematik ve matematik öğretimine ilişkin tutumlarını inceledikleri çalışmasında erkek öğrencilerin kadın öğrencilerden daha olumlu tutuma sahip olduklarını ortaya koymuştur.…”
Section: Tartişma Ve Sonuçunclassified
“…Öte yandan, araştırmaya katılan sınıf eğitimi lisans öğrencilerinin sınıf düzeyi değişkenine göre matematik öğretimine ilişkin tutumlarında anlamlı farklılaşma olmadığı görülmüştür. Bu sonuç ilgili literatür ile de benzerlik göstermektedir (Tabuk, 2018;Tabuk & Tabuk, 2018b). Örneğin; Tabuk (2018) çalışmasında sınıf eğitimi lisans öğrencilerinin matematik öğretimine yönelik tutumlarının sınıf seviyesine göre değişmediği sonucuna ulaşmıştır.…”
Section: Tartişma Ve Sonuçunclassified
See 2 more Smart Citations